Dampak Aktivitas Wisata Ladang Budaya Terhadap Pendapatan Masyarakat - Adi Sucipto; Lukman (Prodi Administrasi Negara FISIPOL Universitas Kutai Kartanegara, 2021)
Tourism is an important sector in supporting economic growth and contributing to increasing the countrys foreign exchange. East Kalimantan is one of the tourist destinations in Indonesia which has cultural and tourism potential that is no less interesting than other tourist destinations in Indonesia. Nearly 90% of tourist attractions are available by nature, and the other 10% are artificial attractions. One that is quite a trend is the Tenggarong Cultural Field tourism object which is commonly called Ladaya. If you look at the data on the number of visits to the Tenggarong Cultural Field tourism object at the beginning of 2020, precisely in January before the covid-19 pandemic, there were around 78,083 people and during the Covid-19 pandemic the number of tourist visits decreased by 6,310 people. The purpose of this study is to examine more deeply about the impact of these tourism activities on the economy caused by the economy of the surrounding community, especially if you look at the number of visits that are quite busy visiting these attractions. The method used in this research is qualitative. Based on the research data, it can be concluded that the activities of the Tenggarong Cultural Field tourism object greatly affect the increase in the income of traders. However, in early 2020, traders experienced a decline in income, because it was caused by the Covid-19 pandemic which could not be conditioned. In addition, the functioning of all outbound rides and cottages at the Tenggarong Cultural Field also has an influence on the number of tourist visits. Keywords: Tourism, Impact, Community Income.